Separate Basic Questions for Assessing the Purposes (Grounds) of Detention of an Accused Located Outside the Borders of the Republic of Armenia - Hovhannisyan, Armen (Bulletin of Yerevan University C: Jurisprudence, 2024)
In this article, the author examined the issues of assessing the purposes (grounds) of the detention of the accused outside the Republic of Armenia. Based also on the study of international documents, the author came to the conclusion that when discussing the issue of detention as a preventive measure of the accused outside the Republic of Armenia, a similar approach cannot be applied to assessing the purposes (grounds) of detention as in the case with the participation of the accused. In this context, the author presented his observations regarding the assessment of the purposes (grounds) of detention in this case. In particular, the author noted that in the case of the accused who is outside the borders of the Republic of Armenia, when solving the issue of applying detention as a preventive measure, it is necessary to first find out and in the context of the purpose of the detention provided for in Article 116, Part 2, Clause 1 of the Criminal Procedure Code of the Republic of Armenia, evaluate whether it is possible to make a reasonable assumption from the proceedings materials that the accused before leaving the territory of the Republic of Armenia was informed (or should have been informed) about the started (in some cases, to be started) legal proceedings: in the case of a negative answer, in the author’s opinion, the petition itself is subject to rejection, and in the case of a positive answer, the presence or absence of an opportunity to obstruct the proceedings or prevent the commission of a crime, in the author’s opinion, is subject to assessment with the participation of the accused when reconsidering the issue of applying detention as a preventive measure in the manner provided for in Part I of Art. 290 RA Code of Criminal Procedure.